Pengaruh Variasi Temperatur Artificial Aging terhadap Sifat Mekanik Sambungan Las Busur Tungsten Gas (GTAW) Pipa Aluminium 6063 - Misbahul Mu’min; Viktor Naubnome; Siswadi Siswadi; Rizki Fauzi (CV. IRA PUBLISHING, 2025)
Aluminum alloy series 6000, especially AA 6063, is widely used in pipe construction because of its light weight, corrosion resistance, and weldability with Gas Tungsten Arc Welding (GTAW) process. This study aims to determine the effects of variations in the heat-treatment temperature during artificial aging on the tensile strength and hardness of 6063 aluminum pipe weld joints. The artificial aging temperature variations used were 150°C, 175°C, and 200°C with a holding time of 30 minutes. The results showed that aging at 200°C produced the highest ultimate tensile strength (UTS) of 181 MPa and the highest hardness in the base metal (BM) area of 70.5 HV.